Polymer extrusion - Lafleur, Pierre G., 1957-; Vergnes, Bruno (London : ISTE-Wiley, 2014)
Extrusion is by far the most important and the oldest processing and shaping method for thermoplastic polymers. This process concerns almost all synthetic polymers, as well as elastomers or food materials. Single-screw extrusion is mainly used nowadays to manufacture finished goods or semi-finished products. More than 90 million tons of thermoplastics are therefore processed every year. Twin-screw extrusion may be divided into two systems: contra-rotating systems used within the context of PVC extrusion, for the manufacture of pipes or profiles; and co-rotating systems experiencing nowa.
4.9. BibliographyChapter 5. Profile Extrusion; 5.1. Profile extrusion; 5.1.1 Different types of profile dies; 5.1.2. Flow calculation inside profile dies; 5.1.3. Evaluation of post-extrusion phenomena; 5.1.4. Design of extrusion dies; 5.2. Pipe extrusion; 5.2.1. Introduction; 5.2.2. Flow calculation; 5.3. Calibrators; 5.3.1. Friction calibrators; 5.3.2. External compressed air calibrators; 5.3.3. External vacuum calibrators; 5.3.4. Internal calibrators; 5.4. Conclusion; 5.5. Bibliography; Chapter 6. Production of Films and Sheets; 6.1. Introduction; 6.2. Cast film extrusion; 6.2.1. Processing.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (Wiley, viewed July 10, 2014)
Keywords: Polymers -- Extrusion; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Polymers -- Extrusion; Plastics -- Extrusion; Plastics; Electronic books; Electronic books